Halide-coupled double electron transfer with electron-rich diboranes - Filbeck, Erik; Cremer, Sebastian; Jansen, Moritz C. F.; Kaifer, Elisabeth; Himmel, Hans-Jörg (Chemistry - a European journal, 2023)
The ditriflato-diborane B2(μ-hpp)2(OTf)2 (hpp=1,3,4,6,7,8-hexahydro-2H-pyrimido[1,2-a]pyrimidinate) acts as a stable surrogate of the elusive dication [B2(hpp)2]2+, being both electrophilic (vacant boron p orbitals) and nucleophilic (filled B−B bond orbital). This combination of seemingly contrasting behaviors could be used to develop a metallomimetic diborane chemistry, with Lewis σ-basic and π-acidic substrates being bound and reduced at the diborane. Here, we report on a novel reaction type within this general theme, in which double electron transfer from the diboron unit to the boron-bound organic substrate is coupled with halide transfer in the other direction. Novel diborylated dienamines are synthesized in this way. The scope of this unprecedented reaction motif and the reaction pathways are elucidated.